Claiming a Space In the Law School Curriculum: A Casebook on Sex-Based Discrimination - Kay, Herma Hill (Columbia Journal of Gender and Law, 2013)
We are gathered here today to celebrate the 40th anniversary of Justice Ginsburg’s appointment in 1972 as Columbia’s first woman law professor. That auspicious date also marks the beginning of my collaboration with her on a law school casebook published in 1974 on the newly-created subject of sex-based discrimination.’ Linda Kerber traced the general history of this and other casebooks that appeared about the same time2 in her wonderfully insightful historical essay, Writing Our Own Rare Books, presented at a symposium held at Yale Law School in April 2000.3 In recalling those heady times today, I will offer a more detailed account of how our first edition came into being, as well as a comparison of how its coverage-and the subject itself-has changed over the ensuing thirty-eight years.